2007
DOI: 10.1111/j.1365-3040.2007.01734.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the MYB‐related transcription factor, PHR1, leads to enhanced phosphate uptake in Arabidopsis thaliana

Abstract: Plants have evolved a number of adaptive strategies to cope with fluctuations in phosphorus (P) supply. The current knowledge of the transcriptional regulation of the P-starvation response in plants is limited. However, one MYB-related transcription factor, PHR1, is known to be involved in the P-starvation response. In this paper, we characterize a T-tagged phr1 knockout mutant and a series of transgenic plant lines which over-express PHR1 in wild type (WT) and phr1 mutant background. The knockout mutant has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
229
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(256 citation statements)
references
References 60 publications
23
229
1
3
Order By: Relevance
“…The Myb-type transcription factor PHOSPHATE STARVATION RESPONSE1 (PHR1) is a conserved key regulator, directly controlling a subset of Pi deficiency genes by binding to an imperfect palindromic sequence motif and thereby activating these genes (Rubio et al, 2001). Consistent with a critical regulatory role, overexpression of PHR1 led to increased Pi accumulation (Nilsson et al, 2007). The activity of PHR1 is controlled by the SUMO E3 protein ligase SIZ1 (Miura et al, 2005), representing the most upstream component of the Pi deficiency signaling cascade identified thus far.…”
mentioning
confidence: 93%
“…The Myb-type transcription factor PHOSPHATE STARVATION RESPONSE1 (PHR1) is a conserved key regulator, directly controlling a subset of Pi deficiency genes by binding to an imperfect palindromic sequence motif and thereby activating these genes (Rubio et al, 2001). Consistent with a critical regulatory role, overexpression of PHR1 led to increased Pi accumulation (Nilsson et al, 2007). The activity of PHR1 is controlled by the SUMO E3 protein ligase SIZ1 (Miura et al, 2005), representing the most upstream component of the Pi deficiency signaling cascade identified thus far.…”
mentioning
confidence: 93%
“…2). In Arabidopsis, overexpression of PHOSPHATE STARVATION RESPONSE1 (PHR1), a master TF controlling a large subset of Pi stressresponsive genes, including PHT genes, resulted in a 2.5-and 4-fold increase in shoot Pi accumulation, under Pi-sufficient and Pi-stress conditions, respectively (Nilsson et al, 2007). Such increases have been associated directly with increased transcript levels of AtPHT1;7, AtPHT1;8, and AtPHT1;9, confirming that Pi acquisition is a concerted action between several transporters and that their individual overexpression might not be sufficient to have a significant impact on Pi content and plant growth.…”
Section: Pi Signaling Pathway Componentsmentioning
confidence: 99%
“…The classic example of transcriptional regulation of P-responsive genes was delineated through studies of the MYB coiled-coil TF phosphate starvation response gene PHR1 (Rubio et al, 2001;Miura et al, 2005;Nilsson et al, 2007;. Rubio et al (2001) identified an Arabidopsis mutant, phr1, that when grown under P deficiency had reduced accumulation of anthocyanin and defective expression of P deficiency response genes.…”
Section: Transcription Factors Involved In P Perceptionmentioning
confidence: 99%